Modified Small Incision Cataract Surgery and Intraocular Lens Implantation in HIV Patients. (January 2015) - Giles, Kagmeni; Domngang, Christelle; Nguefack-Tsague, Georges; Come, Ebana Mvogo; Wiedemann, Peter
Aim: To describe a surgical technique suitable for cataract surgery in regions with a high prevalence of HIV infection. Methods: We reviewed the medical records of 20 consecutive AIDS patients with cataract who underwent modified small-incision cataract surgery (mSICS) with posterior chamber lens implantation. Classic extracapsular cataract extraction (ECCE) was compared to mSICS. The number of potentially risky steps for contamination during surgery and duration of surgery were analyzed. A risky step was defined as any time when the surgeon had to use a sharp instrument. Student's paired t -test was carried out to compare continuous variables, and P -values <0.05 were considered statistically significant. Results: Twenty patients were included in the study, 13 males (65%) and seven females (35%). The mean age was 46.3 ± 13.6 years (range 22–70 years). The number of potentially risky steps for contamination was significantly higher in the classical ECCE than in mSICS ( P < 0.001). The mean duration of cataract surgery with mSICS was significantly shorter as well ( P < 0.001). Conclusion: Conversion to mSICS is essential in order to reduce accidental injuries during cataract surgery in sub-Saharan countries. Sharp instruments should be passed through a neutral zone to ensure that the surgeon and nurse do not touch the same instrument at the same time.